СОСТАВ, УСЛОВИЯ ОБРАЗОВАНИЯ ИЗВЕСТКОВО-ЩЕЛОЧНЫХ ГРАНИТОВ И ПРОБЛЕМЫ ГЕНЕЗИСА НЕОАРХЕЙСКОЙ КЕЙВСКОЙ ЩЕЛОЧНОЙ ПРОВИНЦИИ КОЛЬСКОГО ПОЛУОСТРОВА - Vetrin, V. R.; Belousova, E. A. (Zapiski RMO (Proceedings of the Russian Mineralogical Society), 2021)
Calc-alkaline granites of the Neoarchaean Keivy alkaline province with the U-Pb age of 2667 ± 8 Ma are chemically related to high-potassium calc-alkaline, ferrous, high-alumina granites. Their whole-rock composition is typical of I-type granites. The parental magmas of granites formed as a result of dehydration melting of dacite-tonalite and metagraywacke protoliths, where T 850–950 °C and P ≥ 8 kbar conditions are consistent with formation in the middle crust or at the boundary between the middle and lower crust. The two-stage Hf model age (t DM C ) of zircon within 3.07–3.21 Ga range, suggesting that rocks of the Archaean complex of the Kola Superdeep Borehole and its adjacent areas could be possible associated with the Mesoarchaean rocks of the Keivy megablock basement. Mean εHf(t) values in zircon from calc-alkaline granites (0.2 ± 0.4) coincide within analytical uncertainty with mean εHf(t) values in zircon of comparable U-Pb age from quartz monzonites (–0.5 ± 0.6), subalkaline granites (–0.5 ± 0.5), alkaline granites of the White Tundras (–0.3 ± 0.6) and Ponoy (0.6 ± 0.7) massifs and indicate a relatively enriched source, which has a Hf-isotopic composition similar to that of CHUR. The similarity of the Hf-isotopic composition in zircon from rocks of different composition could be a result of the formation of their initial melts during the melting of the crust with the Hf-isotopic composition close to zero when mafic melts of plume genesis were introduced into the crust.